(untitled) - Caves, Richard E. (New York, 1990)
The book builds models to explain the links between national economies and to show how nations' policies can yield maximun wafare and stability. It begins with the simplet model of trade between nations; builds into this simple model various explanations of the nation's production apparatus; considers tariffs and other controls on trade, identifying their effects and asking in what circumtances they might be desirable from the controlling nation's point of view. The book also presents the theory of control on trade and its applications to present-day trade policies; presents models of short-run desequilibrium and adjustment in order to understand what happen when income and expenditure are not equal, or when money prices are sticky; addresses international movements of maney and holdings of foreign currency reserves; examines international capital movements; considers exchange rate determinants. Following the final chapter of the book is a group of supplements to the principal theoretical chapters of the book
Keywords: Chính sách thương mại,Commercial policy